Ambiguitas yang Mencerminkan Rasisme dalam Film The Princess and The Frog - Oktarina, Rizki Nurmaya (Paradigma: Jurnal Kajian Budaya, 2014)
Princess fairy tales have made the Disney Corporation so famous. At fi rst, Disney princesses were white skinned. As time goes by, Disney started fi lming animated movies with colored princesses. In 2009, Disney released a movie based on an African-American princess named Tiana in ‘The Princess and the Frog’ (2009). Ambiguities in terms of understanding black appear in the fi lm. To help analyzing this movie, Barthes’ semiotics theory will be used. By using that theory, the writer proposes that on one hand, Disney conveys that America has become “color blind,” but on the other, blacks are positioned as lower class. This movie refl ects Disney’s belief in what is true and ideal about the American society, but here we see that the notion “all men are created equal” writt en in the declaration of Independence is not fully implemented in the American society.